EMPIRICAL EVIDENCE ON THE IMPACT OF MONETARY POLICY ON NATIONAL ECONOMIC GROWTH - Abdul Kadir Arno; Nirwana Halide; Iksan Purnama; Akbar Sabani (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2020)
This article discusses empirical evidence of—-imonetary —–ipolicy's impact—-ion national—-ieconomic growth—-iin the decade 2010-2019. This article is analyzed using a regression analysis tool. This article concludes that 1) the interest rate (BI Rate) has—-ian—iimpact rate—-ion national—-ieconomic—igrowth—iin—-ithe decade 2010-2019 of only 7 percent. Impact—–iof US —-iexchange—-irate—ion—-ithe domestic—-ieconomic—-igrowth—iof only 90 percent 3) Impact of the amount of money in circulation on the national economic growth of only 76.8 percent, 4) Impact—-iof—-iinflation—-irate—-ion—-ithe domestic economic growth of only 4.3 percent 5) impact of total investment in national economic growth is only 60.8 percent. Thus—–ithe—-imain—–iobjective—–iof—–imonetary—–ipolicy is more emphasis—–ion—–iprice—–istability. With the first consideration, with output determined by long-term economic capacity, all systems that encourage economic growth will create inflation so that it will not affect real economic growth. Second, the rational financial agent understands that policymakers' actions in supporting the economic growth that helps increase can lead to time consistency problems. Third, monetary policy influencing economic variables takes a long time and has a lag. Fourth, price stability can encourage creating a better economic climate because it will reduce costs from inflation